Issues on digital trade - Ramonette B. Serafica; Jose Ramon G. Albert (Philippine Institute for Development Studies (PIDS), 2018)
From trade in goods then trade in services, we now have digital trade. While there is no universally accepted definition, an emerging consensus on the scope of digital trade is that it includes all cross-border resident/non-resident transactions that are either digitally ordered, online platform enabled, and/or digitally delivered. Since it is a new and still evolving form of trade, the conceptual and measurement issues remain challenging and will continue to be so with innovations in technologies and business applications. Nonetheless, there are various strategies, policies and activities that the Philippines can pursue to keep up with technological advances and take advantage of the opportunities associated with digital trade. We should continue to exploit our strength in ICT and ICT-enabled services while at the same time develop new sources of export growth, particularly in digital products. To ensure that the benefits of e-commerce and digital trade are more widely enjoyed, constraints in terms of etrade-readiness should be addressed. The inhibiting factors are not limited to connectivity although it is perhaps the most critical problem for the Philippines at this stage. Policy gaps and regulatory restrictions should be reviewed to create an enabling environment for digital trade.
Keywords: 330; digital trade; e-commerce; data flows; ICT